Facilitating stakeholder engagement in innovation platforms : an ecosystem perspective within the South African health context - Edlmann, Frederick Robert Peter (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.